Thursday

April 17, 2014

April 17, 2014

Posted by **Josh** on Tuesday, July 24, 2012 at 12:22am.

- Math -
**Reiny**, Tuesday, July 24, 2012 at 12:46ammultiply each term by b^2 - 1 , which is (b+1)(b-1) to get

b+27 - 1(b-1) = (b-2)(b+1)

b+27 - b + 1 = b^2 - b - 2

b^2 -b -30 = 0

(b-6)(b+5) = 0

b = 6 or b = -5

**Related Questions**

math-matrix equations - I have a problem with the following homework question: ...

Algebra - Factor: 3x^2 - 27 3x^2-27=0 27+(3x^2-27)=0+27 3x^2=27 (3x^2)/3=27/3 x^...

Math - What are the multiples of 27? any number that can be divided by 27 9 , 3...

math,algebra,help - can someone explain to me why (3)/(5) and (27)/(45) are ...

Algebra - The book said to replace the x with a zero. Why are two zero's used in...

Math(Please help) - f(x,y)= 10x^1/3 y^2/3 Compute (27,64) so 10(27)^1/3 * (64)^...

math - Make a tally chart for the number of students in the third-, fourth, and ...

math - make a tally chart for the number of students in the third,fourth,and ...

math - make a tally chart for the number of students in the third, fourth ,and ...

MATH - MAKE A TALL CHARTT FOR THE NUMBER OF STUDENTS IN THE THIRD FOURTH AND ...